2010
DOI: 10.1589/jpts.22.203
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Abdominal Muscles during Abdominal Hollowing in Four Different Positions

Abstract: Abstract. [Purpose] This study examined the activities of the rectus abdominis (RA), external abdominal oblique (EO), transversus abdominis and internal abdominal oblique (TrA/IO) while abdominal hollowing (AH) was performed in four different positions (crook lying, prone lying, four-point kneeling, wall support standing).[Subjects] Experiments were conducted on 36 healthy male adults (mean age=24.44 years) who voluntarily agreed to participate in the experiments.[Methods] Each subject was instructed regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
(46 reference statements)
1
7
0
Order By: Relevance
“…The wall support standing showed the smallest increase of TrA thickness in the experimental group. The reason for this difference seems to be that the wall support standing position in Mew's study had a narrower, more unstable base than the wall support standing position in the present study, and Mew's study used the modified AHE of Critchley 29) that also contracts the pelvic floor. Thus, the TrA activity increased more in his study than in the wall support standing of the present study, which decreased the role of the other two muscles in supporting and maintaining the positions.…”
Section: Table1mentioning
confidence: 61%
“…The wall support standing showed the smallest increase of TrA thickness in the experimental group. The reason for this difference seems to be that the wall support standing position in Mew's study had a narrower, more unstable base than the wall support standing position in the present study, and Mew's study used the modified AHE of Critchley 29) that also contracts the pelvic floor. Thus, the TrA activity increased more in his study than in the wall support standing of the present study, which decreased the role of the other two muscles in supporting and maintaining the positions.…”
Section: Table1mentioning
confidence: 61%
“…Rackwitz et al14 ) asserted that selective contraction of the musculus transversus abdominis muscle was necessary to heighten therapeutic performance, but the muscle is difficult to contract selectively15 ) . The musculus transversus abdominis muscle became thicker not only in the BTG but also in the PBUG and RUSIG.…”
Section: Discussionmentioning
confidence: 99%
“…Only those who accurately performed the ADIM along with the contraction of the pelvic floor using a PBU in a supine position were instructed to perform the ADIM in WSS. Because the degree of upper extremity movements in WSS may affect the activity of the TrA ( Park and Lee, 2010 ), the upper extremities were placed in gentle contact with the trunk to control the movements.…”
Section: Methodsmentioning
confidence: 99%
“… Bjerkefors et al (2010) reported increasing selective activity of the TrA from the rectus abdominis (RA) located in the superficial layer while 5 different trunk stabilization exercises performed with the ADIM. In addition, Park et al (2010) also reported that when people with lumbar extension rotation syndrome performed the ADIM with knee flexion in a prone position, their LBP, pelvic movements and trunk extensor activity decreased while the activity of their knee flexors increased. As such, the ADIM is applied in combination with diverse exercises as a way to increase the effects of exercises.…”
Section: Introductionmentioning
confidence: 96%